Isolation, Identification and Distribution of the Gram-Positive Bacterial Isolates Contaminating the Drinking Water of Al Gedarif City, Sudan - M., Abdel-Rahim A.; J., Abdel Daim Z.; A., Ahmed A. (Gezira Journal of Engineering and Applied Sciences, 2011)
In this study, the possible aerobic Gram-positive bacteria were isolated from the main sources of the drinking water in Al Gedarif city (raw and treated waters of Atbara River, main reservoirs and zeer waters of all sources). The isolates were identified using the manual identification tests (primary and biochemical). The primary tests identified the isolates up to the genera level. The results indicated that the isolates belonged to four genera ( Staphylococcus , Micrococcus , Bacillus and Corynebacterium ). However, the biochemical tests identified the isolates up to the species level. The species identified included three of the genus Staphylococcus , four of the genus Micrococcus and eight of the genus Bacillus , as well as the bacterium Corynebacterium diphtheriae . The study also included the distribution of the identified species in the different sources. It was found that Staphylococcus aureus and S. epidermidis were found in almost all sources. However, the other bacterial species were detected in some of the sources and absent in the others. On the other hand, S. saprophyticus , M. varians , M. kristinae , B. thuringiensis , B. pantothenticus and B. firmus were not detected in any of the underground sources.